HUBUNGAN TINGKAT PENDIDIKAN DAN PELATIHAN DENGAN KEAKTIFAN KADER POSYANDU DI WILAYAH KERJA PUSKESMAS PUNGGUR KABUPATEN LAMPUNG TENGAH TAHUN 2013 - Vresti Rahma Dewi; Arie Nugroho; Sefanadia Putri (Holistik Jurnal Kesehatan, 2019)
The Making of banana skin extract with the addition of red beans as a form of waste utilization banana skin in order to be a functional product. banana peel is a waste material that is quite numerous which is about 1/3 of an unpeeled banana, whereas until now the banana peel has not been fully utilized. The method used is Complete Random Rangcangan (RAKL) with four repetitions in the manufacture of its products. This study uses six treatments were 0% (R) as a control, 10% (F1), 20% (F2), 30% (F3), 40% (F4), 50% (F5) to obtain an acceptable product by organoleptic most preferred is then compared with the control.Further controls (R) and a sample of the most preferred protein content analysis test was done using methods khejdalh and calcium levels using titrimetric method.Based on the results of organoleptic test conducted on color, flavor, aroma, konsisensi, and overall acceptance juice products banana peel with the addition of red beans that extracts the banana peel of the most preferred panelists that with the addition of red beans by 40% with the results of the test levels of calcium 3,072 mg and test results protein content of 2.81%. Need to do research on the addition of stabilizers to produce extract banana skin has the best consistency